Economic Valuation of Hunter Access on Mississippi Wildlife Management Areas: Discrete-Count Data Modeling. Issue 5 (1st October 2016) - Hussain, Anwar; Munn, Ian A.; Edwards, Scott L.; Hunt, Kevin
Abstract: Wildlife management areas (WMAs) provide a significant portion of the publicly available hunting sites in Mississippi. Using discrete-count data modeling, this research investigated factors that influence a hunter's choice of a WMA on each trip and trip frequency during a hunting season. The parameter estimates were used to determine changes in compensating variation associated with marginal changes in WMA attributes and the closing of most visited WMAs in each physiographic region of the state. The results should promote resource management in WMAs that is consistent with the welfare of hunters.